2010
DOI: 10.1094/mpmi-03-10-0051
|View full text |Cite
|
Sign up to set email alerts
|

A Yeast STE11 Homologue CoMEKK1 Is Essential for Pathogenesis-Related Morphogenesis in Colletotrichum orbiculare

Abstract: Several signal transduction pathways, including mitogen-activated protein kinase (MAPK) pathways, are involved in appressorium development in Colletotrichum orbiculare, the causal agent of cucumber anthracnose disease. In this study, CoMEKK1, a yeast MAPK kinases (MAPKK) kinase STE11 homolog, was identified as a disrupted gene in an Agrobacterium tumefaciens-mediated transformation mutant. The phenotype of comekk1 disruptant was similar to that of cmk1, a Saccharomyces cerevisiae Fus3/Kss1 MAPK homolog mutant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…More recently, the MAP3K MEKK1 (Cor-Ste11 according to our proposed nomenclature) was found to act upstream of the MAPK Cmk1 (here renamed Cor-Kss1) in C. orbiculare (Sakaguchi et al, 2010). C. orbiculare strains lacking Ste11 and Kss1 both fail to form an appressorium, while nuclear localization of a Kss1-green fluorescent protein fusion is diminished in the ste11 deletion mutants.…”
Section: Kss1/fus3-type Mapks In Other Phytopathogenic Fungimentioning
confidence: 99%
“…More recently, the MAP3K MEKK1 (Cor-Ste11 according to our proposed nomenclature) was found to act upstream of the MAPK Cmk1 (here renamed Cor-Kss1) in C. orbiculare (Sakaguchi et al, 2010). C. orbiculare strains lacking Ste11 and Kss1 both fail to form an appressorium, while nuclear localization of a Kss1-green fluorescent protein fusion is diminished in the ste11 deletion mutants.…”
Section: Kss1/fus3-type Mapks In Other Phytopathogenic Fungimentioning
confidence: 99%
“…One of the cascades, the Chk1-type MAPK cascade, has been focused on as a master regulator of pathogenesis in plant pathogens (Xu 2000;). In many model species of plant pathogen, the Chk1-type MAPK was well characterized (Xu and Hamer 1996;Mayorga and Gold 1999;Mü ller et al 1999;Takano et al 2000;Zheng et al 2000;Bruno et al 2004), although the upstream two kinases, Ste11-type MAPKKK and Ste7-type MAPKK have only been characterized in a few models (Banuett and Herskowitz 1994;Andrews et al 2000;Kim et al 2000;Zhao et al 2005;Sakaguchi et al 2010;Schamber et al 2010). In this study, we identified and characterized Ste7 MAPKK of B. maydis, in order to elucidate the functional roles of Ste7, using null mutant strains (Dste7).…”
Section: Discussionmentioning
confidence: 99%
“…cinerea, etc. (Andrews et al 2000;Mü ller et al 2003;Zhao et al 2005;Sakaguchi et al 2010;Schamber et al 2010 (Errede et al 1993;Neiman and Herskowitz 1994;Bardwell et al 1996). In addition, interactions of these proteins with a scaffold protein, which is involved in this signaling cascade, were also elucidated in S. cerevisiae and M. grisea (Choi et al 1994;Park et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations